Sustainable futures: an agenda for action - Kaplinsky, Raphael (Cambridge, UK: Polity Press, 2021)
"How to steer the economy and society to a more sustainable future"--
A Fork in the Road -- The Rise and Fall of the Mass Production Economy -- The Bumpy Ride to Social Decay -- The Collapse of Environmental Sustainability -- Mass Production Runs out of Steam -- Information and Communication Technologies: The Motor of the New Paradigm -- Transformative Change in Practice -- What's to be Done? -- Who Will Do It? Making Change Happen.
Includes index.
Keywords: Sustainable development